If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(y + 4) + -35 = 0 Reorder the terms: 5(4 + y) + -35 = 0 (4 * 5 + y * 5) + -35 = 0 (20 + 5y) + -35 = 0 Reorder the terms: 20 + -35 + 5y = 0 Combine like terms: 20 + -35 = -15 -15 + 5y = 0 Solving -15 + 5y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 5y = 0 + 15 Combine like terms: -15 + 15 = 0 0 + 5y = 0 + 15 5y = 0 + 15 Combine like terms: 0 + 15 = 15 5y = 15 Divide each side by '5'. y = 3 Simplifying y = 3
| 4(2n+1)=6(9n+2)+2 | | g-5/5=4/5 | | (X*0.365)+(X*.2)=100 | | 4x+5/8=5x+5/8 | | 9x-87=6x-9 | | 10-5(n+4)=11 | | -4(v+7)=7v+27 | | 6y+3(y-5)=4(y+1)-3 | | -4(4y-5)+2(2y+10)= | | Y-(1/2)=3/4 | | 0.8(0.1x+0.5)-0.8= | | 0.16(y-4)+0.08y=0.02y-0.2 | | (1+2j)=(1/12-5j) | | 32+112x-16x^2=0 | | 23=-4(n-3)+3(1+2n) | | 0.08(y-3)+0.04y=0.14-0.4 | | (7x-2)(9x+3)= | | 46x-41=7(6x-6)+4x+1 | | 0.50x+0.15(50)=33.5 | | -16*4=x | | -2y-8=6y+8 | | 2X^2-16X+16y+64=0 | | 9x+7=-5+7x+22 | | -5/8x-6=-7 | | (-87x^(1/2)/2)/x^2 | | -2(x-9)-26=-8 | | 7y+2(y-9)=3(y+1)-2 | | 5/10y-36=0 | | (x-5y)(x+5y)= | | 5y^(8/3)+7y^(5/3)-6y^(2/3)=0 | | 8/9-3/7 | | 6/12y+65=0 |